The influence of perception and knowledge factors among youth towards the effectiveness of the Rakan Cop program in Kuala Lumpur - Sulaiman, Suffian; Othman, Jamilah; D'Silva, Jeffrey Lawrence; Sulaiman, Abdul Hadi (2012)
This paper was conducted to know the current status of RAKAN COP program established by Royal Malaysian Police (RMP) in an effort to reduce crime and fear of crime to maintain peace in the country. Three specific objectives have been established (a) to identify the level of perception and knowledge among youth members of RAKAN COP Program, (b) to ascertain the level of effectiveness of RAKAN COP Program, and (c) to determine the relationship between perception and knowledge towards the effectiveness of RAKAN COP Program. A total of 384 youths in Kuala Lumpur was chosen by applying multi stage sampling technique based on the specified characteristics of respondents recommended by the Police Head Quarters, Kuala Lumpur. The study showed that the youth (RAKAN COP's Member) provides an excellent assessment for all variables studied including effectiveness of RAKAN COP program, perception and knowledge. Thus the researchers proposed to RAKAN COP Unit (RMP), to be more proactive in educating the youth in preventing, and managing crime before the arrival of the police in the location of the crime. Researchers also suggested that police needs to give a positive image among the youths, so that they are more confident and willing to engage and commit in any community policing program.